Strength and Thermal Stability of Fly Ash Based Geopolymer Mortar - Hardjito, Djwantoro; Tsen, Man (Construction Publishing House, 37 Le Dai Hanh St, Hanoi, Vietnam, 2008)
This paper presents the engineering properties of geopolymer mortar manufacturedfrom class F (low calcium) fly ash from Kuching, Sarawak, Malaysia, with potassium-basedalkaline reactor. Tests were carried out on 50x50x50 mm cube geopolymer mortar specimens.The results revealed that as the concentration of KOH increased, the compressive strength ofgeopolymer mortar increases. The range of potassium silicate to KOH solution ratio by mass toproduce high strength geopolymer mortar is in between 0.8 – 1.5. This study also found thatgeopolymer posses superior thermal stability at least up to 800°C. The setting time of geopolymer was found dependent on the alkaline concentration.